Quizizz as Indonesian Learning Media During The COVID-19 Pandemic - Nisa, Khairun (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
During the COVID-19 epidemic, this research aimed to improve students’ fundamental Indonesian knowledge using Quizizz as a game-based learning tool. Description qualitative research technique. The study sample consisted of 33 students from the first semester of the Indonesian Language and Literature Education Study Program. The research instrument is multiple-choice questions about standard and non-standard words and Indonesian writing, which is included in the quizizz website. The data analysis technique was carried out in four stages; 1) data collection, data reduction; data presentation; and concluding. Based on the analysis results, it was found that the quizizz learning media in learning Indonesian can increase student interest in learning and is very effective in increasing knowledge of writing or spelling Indonesian and standard Indonesian grammar. Quizizz also prepares lecturers and students for global education expectations. Online interactive games can help enhance language education and boost digital literacy among the youth, both of which are essential for the fourth industrial revolution.